Modeling Water Allocation under Extreme Drought of South-to-North Water Diversion Project in Jiangsu Province, Eastern China - Zeng, Chunfen; Ma, Jingsong; Cao, Minglin; Xu, Chen; Qi, Wanyu; Wang, Lachun (Frontiers in Earth Science, 2020)
Along with China’s economic development and social progress, water scarcity has become increasingly challenging. Optimized allocation of water resources, especially through water transfer project, is one of the important approaches to mitigate water shortages. In this study, authors built a model of water resources allocation simulation and the microcosmic configuration based on complex water network in the east route of the South-to-North Water Transfer Project in Jiangsu Province, East China. Selecting data from the typical years with assurance rate of P = 95%, 75%, and 50%, the simulation of supply and demand of water resources under the present situation and the tapping scenario of planning project was carried out. The results showed that water supply capacity increased while water deficits decreased remarkably for the diversion projects. Under the assurance rate of P = 95%, 75%, and 50%, the rate of water shortage decreased by 10.3%, 8.0%, and 5.2%, respectively. Under the planning work situation, the amount of water increased by 2,800 million m3 even during the period of extreme drought. Based on the results, it also provided an effective plan for the hydraulic engineering to optimize the allocation and management of water resources. It is helpful for policy maker to mitigate water shortage in Jiangsu Province, other areas with water transfer projects in China and other countries.